(untitled) (Perner’s Contacts, 2016)
The paper reports a new perspective on the issue of efficiency of terminals, with the aim of pointing out the possibility of increasing the capacity of the model example intermodal transport terminal Žilina – Teplička nad Váhom. The paper is aimed at evaluating technology service in the terminal, which is one of the many qualitative approaches that can be followed effectiveness terminals.